The effect of audit quality and institutional ownership on tax avoidance in industrial sector companies - Shellina Fatimah Sebrina; Linda Santioso (WIM Solusi Prima, 2026)
This study examines the effect of audit quality and institutional ownership on corporate tax avoidance among Indonesian industrial-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Grounded in Agency Theory, Compliance Theory, and Corporate Governance Theory, the research employs a quantitative causal design with secondary data sourced from audited annual financial reports. Purposive sampling produced a final sample of 11 companies across five observation years, yielding 55 firm-year observations. Tax avoidance is proxied by the Effective Tax Rate (ETR), audit quality is measured by a Big Four/Non-Big Four dummy variable, and institutional ownership is measured as the proportion of shares held by institutional investors. Multiple linear regression analysis using IBM SPSS Statistics reveals that, individually, neither audit quality (β = −0.003; t = −0.658; p = 0.513) nor institutional ownership (β = 0.013; t = 1.238; p = 0.221) exerts a statistically significant effect on ETR. However, both variables jointly produce a highly significant effect on tax avoidance (F = 33.720; p < 0.001; Adjusted R² = 0.548), indicating that the two governance mechanisms together explain 54.8% of the variation in ETR. These findings support a complementary governance perspective in which external audit oversight and institutional shareholder monitoring reinforce one another to deter aggressive tax planning, even though neither mechanism alone reaches statistical significance.